Prämedikation koronarer Risikopatienten: Ergebnisse einer Umfrage - Böttiger, Bernd W.; Motsch, Johann; Fleischer, Franz; Bauer, Harald; Böhrer, Hubert; Martin, Eike (Anästhesiologie, Intensivmedizin, Notfallmedizin, Schmerztherapie, 1996)
Thieme E-Books & E-Journals